دور التشاركية بين القطاع العام والخاص في إعادة تأهيل قطاع الكهرباء في سورية - الفياض, حسن (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يهدف البحث إلى تعريف مفهوم التشاركية بين القطاع العام والخاص، وتحديد أشكال وأنواع عقودها بميزاتها وعيوبها، والإضاءة على أهم تجارب البلدان المختلفة، وتحديد المسؤوليات التي تقع على كل طرف من أطراف التشاركية.كل ذلك بهدف دراسة تطبيق التشاركية في سورية، خصوصاً بعد الأزمة التي تمر بها سورية منذ عام 2011، وذلك من أجل البحث عن مصادر إضافية للتمويل ولتطوير مشاريع البنية التحتية خصوصاً المرتبطة بقطاع الطاقة تحديداً الكهرباء.ويعد قطاع الكهرباء من أكثر القطاعات التي تعرضت للخراب والتدمير، وكان الهدف الأول لأي عملية تخريبية تقوم بها الجماعات الإرهابية المسلحة بالإضافة لقطع الطرقات وتخريب المرافق العامة.الكهرباء هي عصب التنمية، وبدونها لا يمكن القيام بأي عملية تنموية ولا بناء أي مرفق حيوي، وكلما كانت البنية التحتية لمشاريع الطاقة في بلد ما متقدمة، أعطت مؤشراً بأن هذا البلد متطور.ويقدر حجم الأضرار التي تعرض لها قطاع الكهرباء في سورية منذ بدء الأزمة وحتى نهاية عام 2015 بشكل تقريبي بمقدار 430 مليار ليرة سورية، وهذا الرقم يتعرض للزيادة بسبب التعرض المستمر للتدمير وبسبب خسارة الليرة السورية لقيمتها الشرائية، كذلك هذا الرقم كبير جداً مقارنة بحجم الأموال التي ترصدها الحكومة لتمويل الاستثمار، لذا لابد من البحث عن مصادر تمويل إضافية تساهم في عملية تطوير وإعادة تأهيل البنية التحتية لمشاريع الطاقة، فهل من الممكن أن تقدم التشاركية هذه المصادر؟ هذا ما يحاول البحث الإجابة عنه.This research introduce the public-private partnership (PPP), by determine the difference between the types of PPP contracts, and lighting on the most important experiences of main countries to identify responsibilities of each part of contract. In order to study the possibility of using PPP in Syria, within the crisis since (2011). To afford additional resources of funding, to improve the development process of infrastructure projects, especially projects that related to the energy sector, specifically electricity sector.The electricity sector is one of the most sectors exposed to destruction, and it was the first goal of any sabotage carried out by terrorists. this sector suffering by is more than 430 billion Syrian pounds loses, since the start of the crisis until the end of 2015, and this amount is nominated to rise by the time according to many reasons, one of this reasons is exchange rates fluctuations risk. The amount ofdamages is very huge number, comparison to the size of funds that dedicated by the government to finance investment. On the other hand, there is a serious need to additional resources of funding, to finance the development and rehabilitation process of infrastructure projects. Therefore, could the PPP provide these resources? That is what the research is looking for.